Attentional Literacy as a New Literacy: Helping Students Deal with Digital Disarray - Mark Pegrum (The Canadian Network for Innovation in Education (CNIE), 2021)
When students learn online, they do so within a wider context of digital disarray, marked by distraction, disorder and disconnection, which research shows to be far from conducive to effective learning. Specific educational issues include a lack of focus, linked to information overload in an environment characterized by misinformation and disinformation, as well as a lack of connection to the self and others. Arguing that today’s growing focus on digital literacies in education already serves as a partial response to digital disarray, this evidence-based position paper proposes the concept of attentional literacy as a macroliteracy which interweaves elements of now established literacies with the emerging educational discourse of mindfulness. Through attentional literacy, students may gain awareness of how to focus their attention intentionally on the self, the relationship with others, and the informational environment, resulting in a more considered approach to learning coupled with an appreciation of multiple shifting perspectives. Armed with this developing skillset, students stand to benefit more fully from digital educational experiences. Considerations for continuing research in this area include the need to adopt a critical stance on mindfulness, and the need to operationalize attentional literacy for the classroom.